Kelimpahan Mesofauna Tanah pada Tegakan Tanaman Karet (Havea brasiliensis Muell. Arg) di Tanah Gambut yang Ditumbuhi dan tidak Ditumbuhi Mucuna bracteata - Purwanto, Eko; Wawan, Wawan; Wardati, Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the abundance (type and amount) soil mesofauna and rubber tree growth (Havea brasiliensis Muell. Arg) in peat soil with different conditions of Mucuna bracteata. This research has been conducted in peat soil at social plantation area of PT. RAPP Teluk Meranti from January to March 2016. Analysis soil mesofauna and analysis soil carried out in the laboratory of soil science, Faculty of Agriculture, University of Riau. This research used purposive random sampling namely in rubber contained Mucuna bracteata life, Mucuna bracteata dead and without Mucuna bracteata. Determining the plant sample was randomly with diagonal method in order to get 5 rubber trees that are Mucuna bracteata life, 5 Mucuna bracteata dead and 5 without Mucuna bracteata. Data obtained from the calculation and interpretation of the data be stated in tables and analyzed statistically descriptive. The research show that in stands of rubber trees in the peat soil contained Mucuna bracteata life shows number of individual, family and population density (Kp) soil mesofauna is highest compared with Mucuna bracteata dead and without Mucuna bracteata. Abundance of soil mesofauna highest in rubber tree stands on peat soil which are Mucuna bracteata life dominated by the family Macrohelidae, Mucuna bracteata dead dominated by the family Macrohelidae and without Mucuna bracteata dominated by the family Hirudisomatidae. The rubber tree that is Mucuna bracteata life having the average circle stems is larger compared with Mucuna bracteta dead and without Mucuna bracteata. Keywords: soil mesofauna, rubber tree, peat soil and Mucuna bracteata